Bioelectronic platforms for optimal bio-anode of bio-electrochemical systems: From nano- to macro scopes. (November 2015) - Kim, Bongkyu; An, Junyeong; Fapyane, Deby; Chang, In Seop
Highlights: Bio-electronics platforms (BEPs) are suggested to promote scale-up of MFCs. BEPs are divided into three platforms according to their scope. Challenges of each BEP are highlighted and potential solutions are suggested. Future research directions and ideas are proposed to develop research interest. Abstract: The current trend of bio-electrochemical systems is to improve strategies related to their applicability and potential for scaling-up. To date, literature has suggested strategies, but the proposal of correlations between each research field remains insufficient. This review paper provides a correlation based on platform techniques, referred to as bio-electronics platforms (BEPs). These BEPs consist of three platforms divided by scope scale: nano-, micro-, and macro-BEPs. In the nano-BEP, several types of electron transfer mechanisms used by electrochemically active bacteria are discussed. In the micro-BEP, factors affecting the formation of conductive biofilms and transport of electrons in the conductive biofilm are investigated. In the macro-BEP, electrodes and separators in bio-anode are debated in terms of real applications, and a scale-up strategy is discussed. Overall, the challenges of each BEP are highlighted, and potential solutions are suggested. In addition, future research directions are provided and research ideas proposed to develop research interest.